The Political Economy of European Asylum Policies - Martina Burmann; Marcus Drometer; Romuald Méango (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Despite the recognition that asylum policies are partly determined by political economy factors in the destination country, there is little empirical evidence on the precise linkages between those political factors and asylum policies. We shed light on this issue by examining the impact of elections and parties on first-time asylum applications. Our evidence is based on a large bilateral panel data set comprising 12 European destination countries and their 51 most relevant origin countries during the time period 2002 to 2014. Our findings suggest that the number of asylum applicants under left- and right-wing parties converges before elections and differs thereafter. This result is robust to several different specifications and suggests that both left- and rightwing cabinets choose moderate policies before the election and less moderate policies after the election.
Keywords: H11; D72; F22; 330; Electoral cycles; migration policies